The crucible/silicon interface in directional solidification of photovoltaic silicon. (1st May 2017) - Camel, D.; Drevet, B.; Brizé, V.; Disdier, F.; Cierniak, E.; Eustathopoulos, N.
Abstract: Photovoltaic silicon ingots are currently grown in silica crucibles coated with a porous silicon nitride layer which acts as an interface releasing agent between the silicon and the crucible. The interactions between Si and the Si3 N4 coating determine the infiltration and sticking phenomena occurring at the interface and also affect the pollution of Si by the components of the coating. In this investigation the interfacial interactions and microstructure are studied in crystallization experiments performed in crucibles involving high silicon masses (tens of kg) and long contact time between the silicon and the coated silica (tens of hours). It is shown that for long times, a dramatic change in the nature of the coating/Si interface takes place, with the formation of a self-crucible which prevents the direct contact between the silicon and the coating. The stability of the self-crucible is modeled taking into account the capillary and hydrostatic pressures. The influence of the self-crucible on different practical aspects of the photovoltaic silicon crystallization process is discussed. Graphical abstract: Image 1